Impact of COVID-19 on surgical services in a District General Hospital in the United Kingdom: benefits versus drawbacks - El-Abbassy, Islam H.; El-Hakim, Hesham; Wong, Mei Kei; McIntyre, Robert (International Surgery Journal, 2021)
Background: COVID-19 outbreak led to significant changes in health services worldwide. This study aimed to assess the impact of this outbreak on the surgical services in a small District General Hospital and to highlight any benefits that we can take forward. Methods: Data were collected retrospectively comparing the surgical service activity during the two months (April and May 2020) around the peak of COVID-19 first wave in the UK and the similar two-month period the year before when activity was at its usual pre-COVID level. A short questionnaire on the use and satisfaction of remote consultation was circulated to all hospital consultants. Results: The total number of patients presenting to the emergency department in all specialities almost halved during the COVID-19 crisis. The number of emergency surgical admissions decreased. All elective lists were cancelled and more patients were managed conservatively. In April and May 2020, 156 patients had outpatient surgical consultations. Only 14 of them were face-to-face, whereas the rest were done either by telephone or video calls. This is compared to 472 patients who had face-to-face consultations in April and May 2019. The results of the questionnaire showed that over 90% of the consultants felt telemedicine consultations were satisfactory and that they would have an important role in the future. Conclusions: COVID-19 had serious impacts on surgical services regarding cancellation of elective lists and prolongation of waiting time. Despite these drawbacks, the increased confidence with telemedicine services was a significant benefit.